Assessing the Potential of Internet of Things Technologies for Community Development in Afghanistan - Omid Tarashtwal; Sayed Ehsan Shamsi; Zekrullah Popal (Department of Informatics Faculty of Engineering Universitas Malikussaleh, 2026)
The rapid advancement of Internet of Things (IoT) technologies presents significant opportunities for enhancing agricultural productivity and community development, particularly in developing countries like Afghanistan, where traditional farming practices dominate. Despite growing awareness, the adoption of IoT remains limited due to technical, financial, and socio-cultural barriers. This study aims to assess the potential of IoT technologies for community development in the provinces of Samangan and Balkh, exploring both the challenges and opportunities associated with their implementation. A mixed-methods approach was employed, combining surveys with 200 farmers and semi-structured interviews with key stakeholders, including policymakers, agricultural workers, and technology providers. Quantitative data were analyzed using descriptive statistics and cross-tabulations to examine the relationships between demographic factors and IoT adoption. Qualitative data were analyzed through thematic analysis to identify common patterns, challenges, and opportunities influencing adoption. The findings indicate that while 60% of farmers are aware of IoT technologies, only 30% have integrated them into farming practices, primarily for irrigation and soil monitoring. Key barriers include poor internet connectivity, high device costs, limited technical skills, and social resistance. However, farmers expressed strong interest in adoption if provided with training and support, highlighting opportunities for improved resource management, efficiency, and sustainability. In conclusion, addressing technical, financial, and socio-cultural constraints through targeted interventions can promote IoT adoption and foster sustainable agricultural and community development in Afghanistan.